2018
DOI: 10.1016/j.jchemneu.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of striatal desensitization in cortical-limbic hyperglutamatergic TS- & OCD-like transgenic mice

Abstract: Tics and compulsions in comorbid Tourette's syndrome (TS) and obsessive-compulsive disorder (OCD) are associated with chronic hyperactivity of parallel cortico/amygdalo-striato-thalamo-cortical (CSTC) loop circuits. Comorbid TS- & OCD-like behaviors have likewise been observed in D1CT-7 mice, in which an artificial neuropotentiating transgene encoding the cAMP-elevating intracellular subunit of cholera toxin (CT) is chronically expressed selectively in somatosensory cortical & amygdalar dopamine (DA) D1 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Mahone et al ( 91 ) conducted a study that indicated an increase in Glu and GABA levels within the CSTC loop, leading to improved selective motor inhibition in children with TS. Additionally, the study conducted on D1CT-7 mice revealed a direct association between Glu release in the CSTC loop and tic disorder behavior ( 136 ). However, elevated levels of serum Glu and Asp have also been found in children with ADHD ( 137 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mahone et al ( 91 ) conducted a study that indicated an increase in Glu and GABA levels within the CSTC loop, leading to improved selective motor inhibition in children with TS. Additionally, the study conducted on D1CT-7 mice revealed a direct association between Glu release in the CSTC loop and tic disorder behavior ( 136 ). However, elevated levels of serum Glu and Asp have also been found in children with ADHD ( 137 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one of these lines in which transgene expression was restricted to the piriform cortex, somatosensory cortex, and intercalated nuclei of the amygdala, the mice displayed a number of compulsivelike characteristics, including perseveration and repetition of normal behavior patterns and repetitive leaping (Campbell et al, 1999). Further work with this model showed that chronic cholera toxin activation of these D1 receptor-expressing neurons provoked glutamatergic overexcitation of striatal output neurons of the "direct" corticostriatal-thalamocortical pathway (McGrath et al, 2000;Nordstrom et al, 2015;O'Brien et al, 2018). In other animal models, compulsive lever-pressing in the SA model was reduced by a D1 antagonist (Joel and Doljansky, 2003), whereas repetitive species-typical behavioral patterns such as grooming in the rat (Taylor et al, 2010) and nest building in the rabbit (Hoffman and Rueda Morales, 2012) were respectively strengthened by a D1 agonist and reduced by a D1 antagonist.…”
Section: A Probing the Role Of Neurotransmitters In Obsessive-compulsive Disordermentioning
confidence: 99%
“…Additionally, it has been shown that Glu release in the CSTC loop is directly associated with tic disorder behaviour in D1CT-7 mice (TS transgenic model) (O'Brien et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%